2014
DOI: 10.1089/ten.tec.2014.0046
|View full text |Cite
|
Sign up to set email alerts
|

In VivoMagnetic Resonance Imaging of Type I Collagen Scaffold in Rat: Improving Visualization of Bladder and Subcutaneous Implants

Abstract: Noninvasive monitoring of implanted scaffolds is important to understand their behavior and role in tissue engineering, in particular to follow their degradation and interaction with host tissue. Magnetic resonance imaging (MRI) is well suited for this goal, but its application is often hampered by the low contrast of scaffolds that are prepared from biomaterials such as type I collagen. The aim of this study was to test iron oxide particles incorporation in improving their MRI contrasts, and to follow their d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…The relative mean greyscale value was determined using the formula: Relative mean greyscale value = (Greyscale value of the left side)/(Greyscale value of the right side) (Y. Sun, Geutjes, et al, ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The relative mean greyscale value was determined using the formula: Relative mean greyscale value = (Greyscale value of the left side)/(Greyscale value of the right side) (Y. Sun, Geutjes, et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, Y. Sun, Geutjes, Oosterwijk, and Heerschap () described non‐invasive monitoring of cellular behaviour around gelatin scaffolds and their distribution in the bladder and subcutaneous tissue of mice.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported changes in T 2 and/or ADC values to be associated with other mechanisms like ECM architecture remodeling, [24][25][26][27] fibrous tissue formation, [28][29][30] tissue hydration, 26,[31][32][33] and inflammation, [34][35][36] which may occur concurrently with cellular infiltration and hence affect the T 2 and ADC values. Moreover, the relationship between total cellularity, T 2 , and ADC values has also been well documented in the cancer literature.…”
Section: Discussionmentioning
confidence: 99%
“…However, although the study examined plasma concentrations of PICP and ICTP, the changes of collagen type I formation could not directly be observed. Previous studies suggested that MRI or ultrasound can observe the changes in collagen type I formation [29,30]. More medical examinations should be included in further studies.…”
Section: The Physiological Effects Of Eccentric Exercisementioning
confidence: 99%